(untitled) (GYMNASIUM, 2017)
Romania’s ranking on decreasingly lower places in the hierarchy of the countries participating in the last three Olympic Games (OG) raises a lot of questions in regards to the way in which the athletes, the coaches, the sports clubs, the federations, the Ministry of Youth and Sports (MYS), the Romanian Olympic and Sports Committee (ROSC) look at the Romanian team’s training and participation in this important competition. When talking only about the last three editions of OG, when Romania ranked 17th in 2008 (Beijing), 27th in 2012 (London), and 47th at the last edition, in Rio de Janeiro, one can sound the alarm for all the institutions involved. This research started from the following hypothesis: a careful analysis of the Romanian athletes’ participation in the last three Olympic Games could suggest new strategies for their training.